Measures of complexity derived from automata theory for characterising cardiological time series - Kirchner, Jens; Meyer, Wolfgang; Schwab, Jörg; Hensel, Bernhard (Biomedizinische Technik. Biomedical engineering, 2005)
In order to obtain information about the regulatory mechanisms of the human cardiovascular system, measures of complexity are used to characterise heart rate variability. A method introduced by Crutchfield and Young [1] for constructing an abstract automaton, which produces a given time series, is applied to cardiological data. We use measures of complexity derived from this model to detect differences between patients with congestive heart failure (CHF) and a reference group of healthy persons.<br